Optimizing Loratadine Delivery: Development of Niosomal Transdermal Patches - Sailaja, Charan; Bhupalam, Pradeep Kumar (Indian Journal of Pharmaceutical Education and Research, 2025)
Objectives: To improve and optimize loratadine-loaded niosomal transdermal patches with a Box-Behnken Design to enhance drug delivery and evaluate their potential as an effective alternative to oral administration for allergy treatment. Materials and Methods: Span 40 and Span 80. A Box-Behnken Design (BBD) implemented in Design Expert software was employed to assess the impact of these surfactants on vesicle size, zeta potential and drug entrapment efficiency. Additional physicochemical properties of the niosomes were characterized. The optimized formulation was subsequently incorporated into transdermal patches via solvent casting. These patches were evaluated for flexibility, uniformity and weight and their drug release was compared to a conventional transdermal patch. Results: The niosomal formulation LN-14, optimized with Span 20, Span 40 and Span 80, exhibited superior characteristics, including the smallest vesicle size (195±0.55 nm), highest zeta potential (-54.25±0.08 mV) and maximum entrapment efficiency (91.14±2.95%), leading to its selection for transdermal patch development. The resulting patches were consistent in thickness, weight and flexibility, with strong tensile properties. The LRD-loaded niosomal patches demonstrated a sustained drug release profile, with over 40% permeation by the 4th hr and sustained release over 42 hr, showing potential for effective transdermal delivery. Conclusion: The study revealed that niosomal patches demonstrated effective transdermal delivery of loratadine, offering a promising alternative to oral administration with the potential to reduce gastrointestinal adverse effects. These findings suggest that niosomal patches may be a viable approach for the topical treatment of allergies.
Keywords: Box-Behnken design; Entrapment efficiency; Loratadine-loaded niosomes; Niosomal; patches; Transdermal delivery